Effects of cardiopulmonary bypass on immunoglobulin G antibody titres after SARS-CoV2 vaccination. (6th May 2022) - Hayashi, Ryosuke; Takami, Yoshiyuki; Fujigaki, Hidetsugu; Amano, Kentaro; Sakurai, Yusuke; Akita, Kiyotoshi; Yamana, Koji; Maekawa, Atsuo; Saito, Kuniaki; Takagi, Yasushi
Abstract: OBJECTIVES: Patients with cardiovascular disease are vulnerable to severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) infection. Although SARS-CoV2 vaccination may be effective, its impact on surgical patients is not well studied. We investigated the effects of cardiovascular surgery, especially under cardiopulmonary bypass (CPB), on the antibody titres after SARS-CoV2 vaccination. METHODS: A prospective observational study was designed for patients undergoing surgery between July and November 2021. The immunoglobulin G against the receptor-binding domain was measured and antibody preserved rate (APR) was calculated from perioperative titres comparison. RESULTS: Enrolled 63 study patients were divided into 39 undergoing surgery with CPB (Group CPB) and 24 without CPB (Group None). Preoperative vaccines were BNT162b2 (Pfizer/BioNTech) ( n  = 58, 92%) and mRNA-1273 (Moderna) ( n  = 5, 8%). While immunoglobulin G against the receptor-binding domain titres did not significantly decrease after surgery in Group None, they decreased significantly in Group CPB from 21.80 [11.15, 37.85] to 11.95 [6.80, 18.18] U/ml ( P  < 0.001) a day after surgery, 11.40 [7.85, 22.65] U/ml ( P  < 0.001) 14 days after surgery and 7.60 [4.80, 17.60] U/ml ( P  < 0.001) a month after surgery. The APRs a day after the surgery were significantly lower in Group CPB (0.46 [0.41, 0.60]) than in Group None (0.80 [0.68, 0.87]) ( P  < 0.001). CONCLUSIONS: The SARS-CoV2 antibody titres significantly decreased with lower APRs immediately after surgery under CPB. Based on our informative results, careful considerations of vaccination schedule might be required for surgery under CPB. Abstract : Since the first outbreak of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) in December of 2019, a fear and a threat impacted humanity socially and economically.